Evaluation of antibiotic dispensing without prescription by community pharmacies: a simulated patient study - Velusamy, Sivakumar; ShyamSundar, Shiv Sundar; Regi, Virgin Jerry (International Journal Of Community Medicine And Public Health, 2025)
Background: Antibiotics are widely used, but using them without a prescription remains problematic. In India, Despite Schedule H regulations, antibiotics are available in community pharmacies without a prescription, leading to inappropriate use and contributing to the rise of antibiotic resistance. This study aimed to evaluate antibiotic dispensing practices and influencing factors in community pharmacies for Adult Upper Respiratory Tract Infections (URI) and Uncomplicated Acute Diarrhea (UAD) using a simulated patient (SP) approach. Methods: A cross-sectional observational study was conducted at 200 community pharmacies across Coimbatore city, Tamil Nadu, using SPs presenting symptoms of URI and UAD. Chi-square test, unpaired T-test, and binary logistic regression were employed to analyze factors like scenario, location, pharmacy type, and interaction time on antibiotic dispensing. Results: Antibiotics were dispensed without prescription in 76% of pharmacies, with a higher rate for URI (82%) than UAD (70%, p=0.047). Dispensing was more common in pharmacies within a 1–10 km radius (92%) than those farther away (60%, p=0.032). Interaction time averaged 3.8 minutes when antibiotics were dispensed versus 2.3 minutes when not. Erythromycin (33%) and norfloxacin (32%) were the most commonly dispensed antibiotics. Scenario (OR=8) and locality (OR=5) significantly influenced dispensing practices, while pharmacy type had minimal impact. Conclusions: Antibiotic dispensing without prescription is high with higher rates for URI compared to UAD. Factors like locality, symptom enquiry, and interaction time influenced dispensing. Targeted interventions like training, audits, and public awareness are essential to promote rational use and mitigate antimicrobial resistance.